2017
DOI: 10.1051/matecconf/201713500053
|View full text |Cite
|
Sign up to set email alerts
|

Design of Automation System for Ceramic Surface Quality Control Using Fuzzy Logic Method at Balai Besar Keramik (BBK)

Abstract: Abstract. Indonesia is the world's top 10 ceramic users. Currently, the process of ceramic quality inspection in Indonesia, particularly in Balai Besar Keramik (BBK) is still done manually by human vision. Therefore, it is necessary to design a visual inspection system for digital image processing of ceramic automation using a Fuzzy Logic method. Fuzzy model is one method that can be used to determine ceramic surface quality control. This study aims to apply the fuzzy model in the design of automation system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Song et al [17] successfully identified wood-grain defects using histogram features, achieving a recognition rate of 99.8%. Additionally, Putri et al [18] detected defects on ceramic surfaces using the gray-level co-occurrence matrix technique, with an accuracy of 92.31%. Today, image segmentation techniques have been overshadowed by the widespread use of deep learning models, which offer improved segmentation results [19].…”
Section: Related Workmentioning
confidence: 99%
“…Song et al [17] successfully identified wood-grain defects using histogram features, achieving a recognition rate of 99.8%. Additionally, Putri et al [18] detected defects on ceramic surfaces using the gray-level co-occurrence matrix technique, with an accuracy of 92.31%. Today, image segmentation techniques have been overshadowed by the widespread use of deep learning models, which offer improved segmentation results [19].…”
Section: Related Workmentioning
confidence: 99%
“…Industri keramik ini punya kontribusi yang signifikan terhadap penyediaan kebutuhan domestik, perolehan devisa dan penyerapan tenaga kerja [4]. Dilihat dari data ekspor dan impor yang didapatkan dari [12] bahwa volume impor keramik di Indonesia sendiri masih tinggi dibandingkan volume ekspor. Salah satu faktor yang diyakini oleh Asosiasi Aneka Industri dan Keramik Indonesia (Asaki) mengapa adanya ketimpangan antar ekspor dan impor keramik dalam negeri adalah kualitas yang dimiliki.…”
Section: Pendahuluanunclassified
“…Seperti yang dilakukan [3] yang menggunakan teknik pengolahan citra digital dalam mengidentifikasi cacat pada jenis ubin polos dan bertekstur. Selain itu dalam penelitian [12] yang menggunakan teknik yang sama untuk mendeteksi cacat pada permukaan keramik. Serta yang dilakukan oleh [2] yang menggunakan teknik pengolahan citra digital pada keramik untuk mengetahui luas keramik dan cacat keramik untuk dry spot .…”
Section: Landasan Teori a Image Processingunclassified
“…In traditional surface defect detection methods, researchers have focused on various aspects of texture, color, and shape features. For texture features, Putri et al [3] utilized the gray level co-occurrence matrix (GLCM) extraction method to capture the features of ceramic surface quality defects. The extracted data, including autocorrelation, variance, and object count, were processed and inputted into a fuzzy model, achieving a defect recognition accuracy of 96.87%.…”
mentioning
confidence: 99%